Criminal Liability Of Disseminator’s Pornographic Content On Social Media - Helmalia Verena Putri Kanci; Rudepel Petrus Leo; Heryanto Amalo (Catuspata, 2023)
Social media platforms have facilitated unprecedented access to and dissemination of various content, including material that violates societal norms, such as cyberporn, which falls under the realm of cybercrime. The objective of this research is two-fold: (1) to analyze the role of criminal law in addressing cases involving the distribution of pornographic content in terms of both substance and procedure and (2) to determine whether the individuals responsible for spreading such content can be held accountable for their actions. The author employs a normative legal research methodology, primarily relying on library research to explore relevant data, literature, and legal provisions pertaining to the raised legal issues. The results of this study indicate that criminal law plays a crucial role in assessing the dissemination of pornographic content as an offense, aligning with the provisions outlined in Law Number 44 of 2008 concerning Pornography. Additionally, the act of distributing pornographic content via platforms like WhatsApp and Line is deemed a violation of Law Number 11 of 2008 concerning Electronic Information and Transactions, which entails corresponding legal sanctions. Formally, this entails an expansion in the scope and types of admissible evidence beyond what is stipulated in Article 184 of the Code of Criminal Procedure, as well as modifications in the examination process. Regarding the perpetrator involved in the case of JA, who spread pornographic content on social media, they can indeed be held accountable. The perpetrator exhibited an intent to seek revenge against the victim through the dissemination of the pornographic video, thereby meeting the necessary criteria for legal responsibility.